2017
DOI: 10.5194/acp-17-3713-2017
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of triple oxygen isotopic compositions of atmospheric sulfate, nitrate, and ozone at Dumont d'Urville, coastal Antarctica

Abstract: Abstract. Triple oxygen isotopic compositions (Δ17O  = δ17O − 0.52  ×  δ18O) of atmospheric sulfate (SO42−) and nitrate (NO3−) in the atmosphere reflect the relative contribution of oxidation pathways involved in their formation processes, which potentially provides information to reveal missing reactions in atmospheric chemistry models. However, there remain many theoretical assumptions for the controlling factors of Δ17O(SO42−) and Δ17O(NO3−) values in those model estimations. To test one of those assumption… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
81
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(99 citation statements)
references
References 67 publications
(129 reference statements)
13
81
2
Order By: Relevance
“…Previous isotopic studies have reported the Δ 17 O(NO 3 − ) at the coast of Antarctica (Ishino et al, ; Savarino et al, ) and in the interior of Antarctica (Erbland et al, ; Frey et al, ; McCabe et al, ; Savarino et al, ), generally finding a distinctive Δ 17 O seasonal cycle that reflects the higher relative contribution of O 3 oxidation and/or stratospheric input during the austral winter and increased HO x + RO x oxidation during the austral summer. Previous Antarctica δ 15 N(NO 3 − ) measurements indicate a distinctive seasonal cycle driven by localized snowpack emissions during periods of sunlight (Erbland et al, ; Frey et al, ; Savarino et al, ).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Previous isotopic studies have reported the Δ 17 O(NO 3 − ) at the coast of Antarctica (Ishino et al, ; Savarino et al, ) and in the interior of Antarctica (Erbland et al, ; Frey et al, ; McCabe et al, ; Savarino et al, ), generally finding a distinctive Δ 17 O seasonal cycle that reflects the higher relative contribution of O 3 oxidation and/or stratospheric input during the austral winter and increased HO x + RO x oxidation during the austral summer. Previous Antarctica δ 15 N(NO 3 − ) measurements indicate a distinctive seasonal cycle driven by localized snowpack emissions during periods of sunlight (Erbland et al, ; Frey et al, ; Savarino et al, ).…”
Section: Introductionmentioning
confidence: 96%
“…In contrast, the oxygen (O) isotopic composition (δ 18 O & Δ 17 O) is associated with the incorporation of oxygen atoms from various atmospheric oxidants, as gaseous precursors (i.e., NO x and SO 2 ) are oxidized to NO 3 − or SO 4 2− (Alexander et al, ; Michalski et al, ). The number of isotopic studies of NO 3 − or SO 4 2− in polar regions are relatively meager but have received increased attention in recent years, and interpretations of the isotopic signals continue to evolve (Erbland et al, ; Frey et al, ; Hill‐Falkenthal et al, ; Ishino et al, ; McCabe et al, ; Savarino et al, , ). However, to utilize stable isotopes in NO 3 − and SO 4 2− in a paleoclimate context (i.e., ice core studies) in the interior of Antarctica, we must have a better understanding of the isotopic signatures of these molecules in the polar atmosphere.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…SO 2 has 17 O = 0 ‰ due to the rapid isotopic exchange with abundant vapor water whose 17 O is near 0 ‰ (Holt et al, 1981). S(IV) oxidation by H 2 O 2 and O 3 leads to 17 O(SO 2− 4 ) = 0.7 and 6.5 ‰, respectively, on the basis of 17 O(H 2 O 2 ) = 1.4 ‰ (Savarino and Thiemens, 1999) and assuming 17 O(O 3 ) = 26 ‰ (Vicars and Savarino, 2014;Ishino et al, 2017 (Dubey et al, 1997;Luz and Barkan, 2005;Lee et al, 2002;Bao et al, 2000). Sulfate produced by NO 2 oxidation is suggested to occur either via a radical chain mechanism (Shen and Rochelle, 1998), via oxygen-atom transfer from OH − (Clifton et al, 1988), or from O 2 based on experimental results of He et al (2014) (Fu, 2014).…”
Section: Introductionmentioning
confidence: 99%